Rod-like rare-earth metal oxide ruthenium-loaded catalyst for efficient ammonolysis hydrogen production and preparation method of rod-like rare-earth metal oxide ruthenium-loaded catalyst

By loading low-quality ruthenium on rare earth metal oxide support and preparing catalysts by hydrothermal synthesis method, the existing ammonia decomposition catalysts have been solved, and the existing ammonia decomposition catalysts have poor activity and high energy consumption under low temperature conditions are achieved, and the low-temperature and high-efficiency hydrogen production is achieved, with low cost.

CN119793454APending Publication Date: 2025-04-11BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411977403.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing ammonia decomposition catalysts have low ammonia decomposition conversion rate under low temperature conditions, low catalyst activity, high ammonia decomposition temperature, high energy consumption, and high cost.

Method used

Rod-shaped rare earth metal oxides are used as support, and the lower loading of ruthenium (the mass fraction of ruthenium is 0.5 to 2 wt.%, preferably 1%) is used to prepare a catalyst by hydrothermal synthesis method, optimize the molar ratio of raw materials and the hydrothermal synthesis temperature, and prepare a rare earth metal oxide support with a unique nanorod-shaped morphology.

Benefits of technology

100% decomposition of ammonia is achieved at lower temperatures (such as 450°C), the H2 generation rate is higher, and the catalyst cost is lower.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The invention discloses a rod-like rare earth metal oxide ruthenium-loaded catalyst for efficient ammonolysis hydrogen production and a preparation method thereof, and belongs to the field of ammonolysis hydrogen production. The catalyst takes a nanorod-shaped rare earth metal oxide as a carrier, loads a small amount of noble metal ruthenium as an active component, and is applied to hydrogen production through ammonia decomposition. The catalyst disclosed by the invention can efficiently decompose ammonia gas at the reaction temperature of 450 DEG C, and has a relatively high H2 generation rate (50mol. GRu <-1 >. H <-1 >).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy and environment, and specifically to a rod-shaped rare earth metal oxide-supported ruthenium catalyst and a preparation method thereof, wherein the catalyst is applied to the decomposition of ammonia to produce hydrogen. Background Art

[0002] Energy is the foundation and driving force of human civilization progress. my country's existing energy system is still dominated by coal, and fossil energy accounts for a large proportion. Therefore, under the promotion and guidance of the dual carbon policy, the task of energy transformation is arduous and imminent. At present, my country's energy transformation first faces the problem of energy security. Coal, oil, natural gas, etc. are all non-renewable energy sources with limited resource reserves. If they are not used reasonably, they will lead to resource depletion and humans will not be able to cope with energy supply problems. Secondly, there is the environmental problem. my country's carbon dioxide emissions are extremely high, accounting for one-third of the global total. This is related to the structure of my country's energy system. The use of fossil energy will bring a series of environmental pollution problems. The key to solving these two major problems is to find new safe, efficient, clean and low-carbon energy to replace fossil energy, so as to achieve energy transformation and promote high-quality development of the energy structure. Hydrogen energy has a wide range of sources and rich application scenarios. It helps energy renewable, promotes large-scale peak load regulation of power grids and cross-seasonal and cross-regional energy storage, and realizes low-carbonization in all walks of life. It is a clean, efficient, safe and flexible energy with diverse acquisition channels. It can be prepared from multiple sources such as primary energy and secondary energy, and can promote the clean and efficient use of fossil energy. As an energy carrier and energy storage method, hydrogen can be combined with renewable energy to form a low-carbon energy system. It is a combination of deep industrial decarbonization and deep disconnection from the grid for new energy.

[0003] In addition, hydrogen energy has the potential to store energy across time and space, and has a wide range of application scenarios. It is one of the important ways to achieve low-carbon or even zero-carbon in the fields of energy, transportation, and chemical industry. As a new energy source, hydrogen energy occupies an important position in carbon neutrality development, and the development of hydrogen energy is a major strategy for my country's energy system to achieve low-carbon transformation. However, hydrogen has a low volume density and is difficult to liquefy, resulting in high transportation costs and low efficiency; on the other hand, since the large-scale preparation of hydrogen is mainly based on fossil energy as raw materials, the produced hydrogen contains carbon oxides, so the transportation and storage of hydrogen will greatly limit the use of hydrogen energy. Ammonia has significant advantages such as high energy density, low liquefaction storage and transportation costs, carbon-free energy storage, and high safety. It has a wide range of sources and can be used as an efficient hydrogen storage medium, with good development prospects.

[0004] The ammonia decomposition reaction is an endothermic reaction, which usually requires extremely high temperatures to maintain the reaction. Studies have shown that the use of catalysts is beneficial to lowering the decomposition temperature of ammonia. Compared with other methods of decomposing ammonia, it has the advantages of low reaction cost, low energy consumption, and safe operation.

[0005] Ruthenium-based catalysts have great potential for catalyzing ammonia decomposition to produce hydrogen due to their excellent hydrogen activation ability, and are considered to be one of the most effective catalysts for catalyzing ammonia decomposition reactions. Currently, the carriers of ammonia decomposition catalysts mainly include carbon materials, metal oxides and nitrides, but they have problems such as poor activity, poor stability, high reaction temperature and high energy consumption, and are not very effective in the application of catalyzing ammonia decomposition to produce hydrogen.

[0006] CN118513026A discloses a composite oxide supported ruthenium catalyst and a preparation method thereof. The catalyst preparation process is simple and the catalyst is easily available. However, the catalyst has a low ammonia decomposition conversion rate under low temperature conditions, low catalyst activity, a high ammonia complete decomposition temperature, and high energy consumption.

[0007] CN114832819A discloses a mesoporous cerium oxide supported ruthenium catalyst and its preparation method. The preparation process of the catalyst is simple, does not require solvent and has good repeatability. However, the catalyst particles are obviously agglomerated and the catalytic ammonia decomposition activity is insufficient under low temperature conditions.

[0008] Relevant literature (ACS Sustainable Chemistry and Engineering, 2019, 7(9): 8226-8235) reported the use of Ru / Al2O3 and Ru / BHA catalysts for ammonia decomposition to produce hydrogen. It was found that the Ru particle size in the Ru / Al2O3 catalyst was 3.8 nanometers, but the ammonia decomposition activity of the catalyst was low, with a conversion rate of 23% at 500°C.

[0009] CN109954493A discloses a rare earth metal oxide supported ruthenium catalyst for hydrogen production by decomposing ammonia. The catalyst uses ruthenium as an active component and uses rare earth metal oxides such as lanthanum oxide, cerium oxide, praseodymium oxide, and neodymium oxide as carriers. The ruthenium content (the mass of ruthenium element accounts for the mass of rare earth metal oxide) is about 10wt.%, and the catalyst is mainly prepared by precipitation method. However, the ruthenium loading is too high, and the cost of the catalyst is still relatively high.

[0010] In summary, there is currently no high-activity, high-stability catalyst that can completely decompose ammonia into hydrogen at a relatively low cost and at a relatively low temperature. Therefore, the development of a new low-temperature and high-efficiency ammonia decomposition catalyst is of great significance for the development of ammonia decomposition hydrogen production technology. Summary of the invention

[0011] In order to solve the problems existing in the prior art, the present invention provides a rod-shaped rare earth metal oxide-supported ruthenium catalyst and a preparation method thereof. The catalyst has a low ruthenium content and has a high efficiency of hydrogen production by decomposing ammonia under low temperature conditions, and is a highly potential catalyst for hydrogen production by decomposing ammonia.

[0012] In order to solve the problems of the prior art, the present invention provides the following technical solutions:

[0013] A rod-shaped rare earth metal oxide-supported ruthenium catalyst comprises supported active component ruthenium and a rod-shaped rare earth metal oxide carrier, wherein the mass fraction of ruthenium is 0.5-2wt.%, preferably 1%.

[0014] The preparation method of the catalyst comprises the following steps:

[0015] (1) After completely dissolving the rare earth precursor in deionized water, adding alkali under stirring, and continuing stirring for a period of time to obtain a mixed solution;

[0016] (2) transferring the mixed solution obtained in step (1) to a Teflon-lined stainless steel autoclave and reacting it at a certain temperature for a period of time; filtering and washing, collecting the solid sample after the reaction, drying it at a certain temperature, and then transferring it to a muffle furnace for calcination to obtain a carrier rod-shaped rare earth metal oxide;

[0017] (3) adding the prepared rod-shaped rare earth metal oxide support CeO2 into deionized water and stirring to obtain suspension A, dissolving a certain mass of ruthenium precursor in deionized water to prepare solution B, slowly adding solution B into suspension A and stirring for a period of time;

[0018] (4) The solution obtained in step (3) is subjected to a rotary evaporator to remove water at a certain temperature, and then the solution is dried in an oven for a period of time and then transferred to a muffle furnace for calcination for a certain period of time to obtain the rod-shaped rare earth metal oxide-supported ruthenium catalyst.

[0019] Furthermore, the precursor in step (1) is a cerium precursor, and the cerium precursor is at least one of cerium nitrate hexahydrate, cerous chloride heptahydrate, cerium sulfate, and ammonium cerium nitrate; the alkali is one or a mixture of lithium hydroxide, sodium hydroxide, potassium hydroxide, and ammonia water.

[0020] Further, in step (1), the molar ratio of the cerium precursor to the base is 1:30 to 60;

[0021] Furthermore, the stirring time in step (1) is 10 to 60 minutes;

[0022] Furthermore, in step (1), each millimole of the precursor in the mixed solution corresponds to 30-100 ml of water, and more preferably 40-50 ml;

[0023] Furthermore, the reaction temperature in step (2) is 80 to 180° C., preferably 90 to 120° C.; more preferably 100° C.; the reaction time is 12 to 72 hours, preferably 24 hours;

[0024] Furthermore, the calcination temperature in step (2) is 350-550°C, more preferably 450°C, and the calcination time is 1-5 hours;

[0025] There are no special requirements for the filtering, washing method and subsequent drying temperature and time in step (2). The filtering and washing methods are, for example, but not limited to, washing with deionized water and anhydrous ethanol and centrifugation; the drying temperature is, for example, but not limited to, 50 to 110° C., and the drying time is, for example, but not limited to, 12 to 36 hours.

[0026] The ruthenium precursor in the above step (3) is at least one of ruthenium chloride and ruthenium acetate;

[0027] Furthermore, in step (3), the molar ratio of the rod-shaped rare earth metal oxide support to the ruthenium element in the ruthenium precursor is 50 to 60:1;

[0028] Furthermore, the calcination temperature in step 4) is 350-550°C, preferably 450°C, and the calcination time is 1-5 hours;

[0029] The beneficial effects of the present invention are:

[0030] The present invention prepares a rare earth metal oxide carrier with a unique nanorod-like morphology by optimizing the preparation method of the catalyst and accurately controlling the molar ratio of the raw materials and the hydrothermal synthesis temperature. The rare earth metal oxide carrier CeO2 with a nanorod-like morphology has a unique crystal face exposure, a large number of oxygen vacancy defects and a high specific surface area. These excellent properties promote the high dispersion of the ruthenium species loaded on the surface, and confine the ruthenium species during the heat treatment and reaction process, thereby inhibiting the agglomeration and sintering of the ruthenium species. The abundant oxygen vacancies on the surface of the rod-shaped rare earth metal oxide promote the electron transfer between the carrier and the active component, so that the active ruthenium species is in an electron-rich state, which is conducive to the desorption of the ammonia decomposition reaction products N2 and H2, and promotes the reaction to proceed in the forward direction. Even at a relatively low noble metal loading (1wt.%), the rod-shaped rare earth metal oxide-supported ruthenium catalyst (Example 1) provided by the present invention can decompose 100% of NH3 at a relatively low temperature (450°C), and the generation rate of H2 is 50mol·g Ru -1 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of Example 1. Example 1 is a rod-like structure with a diameter of about 20 nanometers and a length of about 150 nanometers.

[0032] Figure 2 This is a scanning electron microscope image of Example 2, which is a nanoparticle structure with a diameter in the range of 20 to 30 nanometers.

[0033] Figure 3 This is a scanning electron microscope image of Comparative Example 1, which is a densely arranged polyhedral structure with different sizes (50 to 300 nanometers). DETAILED DESCRIPTION

[0034] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0035] Catalytic performance test

[0036] 0.2 g of catalyst is taken and loaded into a quartz tube of a fixed bed for hydrogen production by decomposition of ammonia. Quartz wool is loaded at the upper and lower parts of the quartz tube to prevent the catalyst powder from being washed away by the airflow during the reaction. Before the formal ammonia decomposition reaction, the catalyst is reduced at 500° C. for 1 hour in a 50% H2 / He atmosphere, then cooled to 300° C. in a He atmosphere, and a 50% NH3 / He mixed gas is supplied at a volume flow rate of 50 ml / min to carry out ammonia decomposition hydrogen production reaction. The ammonia decomposition hydrogen production reaction is carried out in the range of 300 to 450° C. During the heating process, the catalytic activity of ammonia decomposition is evaluated, and sampling is performed every 50° C. for detection and analysis. The tail gas after the reaction of the fixed bed for ammonia decomposition is passed into an online gas chromatograph to detect its composition and content, and unconverted ammonia is removed with dilute sulfuric acid;

[0037] The activity of the catalyst is expressed by the NH3 conversion rate.

[0038]

[0039] represents the conversion rate of ammonia,

[0040] represents the concentration of ammonia before the reaction,

[0041] Indicates the concentration of ammonia after the reaction.

[0042] The generation rate of H2 is,

[0043]

[0044] is the inlet ammonia flow rate, mL min -1 ;

[0045] m c is the mass of ruthenium in the catalyst, g;

[0046] is the H2 generation rate, mol·g Ru -1 ·h -1, which represents the number of moles of H2 generated per hour by a catalyst containing 1 gram of ruthenium.

[0047] Example 1

[0048] 0.543 g (1.2 mmol) of cerium nitrate hexahydrate was dissolved in 20 ml of deionized water, and 2 g (50 mmol) of sodium hydroxide was dissolved in 30 ml of deionized water and added dropwise to the above solution. The mixture was transferred to a Teflon-lined stainless steel autoclave and reacted at 100°C for 24 hours. After centrifugal filtration, it was washed three times with distilled water and anhydrous ethanol, and finally dried in an oven at 80°C for 12 hours, and calcined in a muffle furnace at 450°C for 4 hours. After the calcination, a rod-shaped cerium oxide carrier was obtained.

[0049] 0.5032 g (2.92 mmol) of rod-shaped CeO2 carrier was weighed and dispersed in 70 ml of deionized water to obtain suspension A, 0.1131 g (0.154 mmol) of ruthenium acetate was dissolved in 50 ml of deionized water to obtain solution B, and then solution B was slowly poured into solution A. After stirring for 0.5 hour, the water was removed by rotary evaporator and then dried in an oven at 80°C for 12 hours. After drying, the sample was placed in a muffle furnace and calcined at 450°C for 4 hours to obtain the rod-shaped cerium dioxide-supported ruthenium catalyst sample with a ruthenium loading of 1% of Example 1.

[0050] Example 2

[0051] Compared with Example 1, the only difference is that the reaction temperature in the preparation process of the cerium dioxide carrier in this embodiment is 180°C, specifically:

[0052] 0.543 g (1.2 mmol) of cerium nitrate hexahydrate was dissolved in 20 ml of deionized water, and 2 g (50 mmol) of sodium hydroxide was dissolved in 30 ml of deionized water and added dropwise to the above solution. The mixture was transferred to a Teflon-lined stainless steel autoclave and reacted at 180°C for 24 hours. After centrifugal filtration, it was washed three times with distilled water and anhydrous ethanol, and finally dried in an oven at 80°C for 12 hours, and calcined in a muffle furnace at 450°C for 4 hours. After the calcination, a cubic cerium oxide carrier was obtained.

[0053] 0.5032 g (2.92 mmol) of cubic CeO2 carrier was weighed and dissolved in 70 ml of deionized water to obtain suspension A, 0.1131 g (0.154 mmol) of ruthenium acetate was dissolved in 50 ml of deionized water to obtain solution B, and then solution B was poured into solution A. After stirring for 0.5 hour, the water was removed by rotary evaporator and then dried in an oven at 80°C for 12 hours. After drying, the sample was placed in a muffle furnace and calcined at 450°C for 4 hours to obtain the granular ruthenium-based cerium dioxide catalyst sample with a ruthenium loading of 1% of Example 2.

[0054] Comparative Example 1

[0055] 0.5032 g (2.92 mmol) of commercial industrial CeO2 carrier was weighed and dispersed in 70 ml of deionized water to obtain suspension A, 0.1131 g (0.154 mmol) of ruthenium acetate was dissolved in 50 ml of deionized water to obtain solution B, and then solution B was poured into solution A. After stirring for 0.5 hour, the water was removed by rotary evaporation and then dried in an oven at 80°C for 12 hours. After drying, the sample was placed in a muffle furnace and calcined at 450°C for 4 hours to obtain the commercial industrial cerium dioxide catalyst sample with a ruthenium loading of 1% of comparative example 1.

[0056] Comparative Example 2

[0057] Dissolve 6 mmol of lanthanum nitrate hexahydrate in 40 ml of deionized water, dissolve 4 g (0.1 mol) of sodium hydroxide in 10 ml of deionized water and drop into the above solution, stir evenly. Transfer the mixture to a Teflon-lined stainless steel autoclave and react at 180°C for 12 hours. After centrifugal filtration, wash with distilled water and anhydrous ethanol three times each, and finally dry in an oven at 80°C for 12 hours, calcine in a muffle furnace at 450°C for 4 hours, and after calcination, obtain a rod-shaped lanthanum oxide carrier.

[0058] Weigh 1 gram (3 mmol) of rod-shaped lanthanum oxide (La2O3) carrier and disperse it in 70 ml of deionized water in a beaker to obtain suspension A, 0.0788 grams (0.107 mmol) of ruthenium acetate is dissolved in 50 ml of deionized water and placed in a beaker to obtain solution B, then pour solution B into solution A, stir for 0.5 hour, remove water through a rotary evaporator, and then transfer to an 80°C oven for drying for 10 hours. After drying, the sample is placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a rod-shaped ruthenium-based lanthanum oxide catalyst sample with a ruthenium loading of 1% of comparative example 2.

[0059] Comparative Example 3

[0060] Weigh 2.175 g (5 mmol) of praseodymium nitrate and dissolve it in 40 ml of deionized water. Dissolve 24 g (0.6 mol) of sodium hydroxide in 260 ml of deionized water and drop it into the above solution, stirring evenly. Transfer the mixture to a Teflon-lined stainless steel autoclave and react at 180°C for 24 hours. After centrifugal filtration, wash it with distilled water and anhydrous ethanol three times each, and finally dry it in an oven at 80°C for 24 hours, and calcine it in a muffle furnace at 500°C for 4 hours. After calcination, a rod-shaped praseodymium oxide carrier is obtained.

[0061] Weigh 1 g (2.87 mmol) of rod-shaped praseodymium oxide (Pr6O 11) The carrier is dispersed in 70 ml of deionized water and placed in a beaker to obtain a suspension A, 0.0788 g (0.107 mmol) of ruthenium acetate is dissolved in 50 ml of deionized water and placed in a beaker to obtain a solution B, and then solution B is poured into solution A, stirred for 0.5 hour, and then transferred to an oven at 80°C for drying for 10 hours via rotary evaporation. After drying, the sample is placed in a muffle furnace and calcined at 500°C for 4 hours to obtain a rod-shaped ruthenium-based praseodymium oxide catalyst sample with a ruthenium loading of 1% of comparative example 3.

[0062] Table 1 Activity evaluation results of examples and comparative examples (ammonia conversion %)

[0063]

[0064] Table 2 Hydrogen generation rate of the embodiments and comparative examples (unit: )

[0065]

[0066] From the results in Tables 1 and 2, it can be seen that the low-loaded ruthenium rod-shaped ceria catalyst prepared in Example 1 is -1 ·h -1 ) has a high ammonia decomposition performance, the ammonia conversion rate is as high as 100% at 450℃, and the H2 generation rate is The performance of the catalyst with rod-shaped ceria as a carrier for hydrogen production from ammonia decomposition is better than that of a cubic ceria catalyst prepared by a similar synthesis method, and is much better than that of a catalyst with commercial industrial ceria as a carrier. Among all catalysts with rod-shaped rare earth metal oxides as a carrier (Example 1, Comparative Examples 2 and 3), the rod-shaped ceria catalyst of Example 1 has the best performance for hydrogen production from ammonia decomposition.

[0067] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A rod-shaped rare earth metal oxide-supported ruthenium catalyst for efficient hydrogen production by ammonia decomposition, characterized in that: The catalyst comprises an active component and a carrier, wherein the active component is ruthenium and the carrier is a rod-shaped rare earth metal oxide; the mass percentage of the active component ruthenium in the catalyst is 0.5-2wt.%, and the rest is the rare earth metal oxide carrier.

2. The method for preparing a rod-shaped rare earth metal oxide-supported ruthenium catalyst for efficient hydrogen production by decomposition of ammonia according to claim 1, characterized in that: The following steps are involved: (1) After completely dissolving the rare earth precursor in deionized water, adding alkali under stirring, and continuing stirring for a period of time to obtain a mixed solution; (2) transferring the mixed solution obtained in step (1) into a Teflon-lined stainless steel autoclave and reacting at a certain temperature for a period of time; Filter and wash, collect the solid sample after the reaction, dry it at a certain temperature, and then transfer it to a muffle furnace for calcination to obtain a carrier rod-shaped rare earth metal oxide; (3) adding the prepared rod-shaped rare earth metal oxide support CeO2 into deionized water and stirring to obtain suspension A, dissolving a certain mass of ruthenium precursor in deionized water to prepare solution B, slowly adding solution B into suspension A and stirring for a period of time; (4) The solution obtained in step (3) is subjected to a rotary evaporator to remove water at a certain temperature, and then the solution is dried in an oven for a period of time and then transferred to a muffle furnace for calcination for a certain period of time to obtain the rod-shaped rare earth metal oxide-supported ruthenium catalyst.

3. The preparation method according to claim 2, characterized in that: Furthermore, the precursor in step (1) is a cerium precursor, the cerium precursor is at least one of cerium nitrate hexahydrate, cerous chloride heptahydrate, cerium sulfate, and ammonium cerium nitrate, and the base is lithium hydroxide, sodium hydroxide, potassium hydroxide, and ammonia water, or a mixture of several of them.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the precursor to the base in step (1) is 1:30-60.

5. The preparation method according to claim 2, characterized in that: In step (1), each millimole of the precursor in the mixed solution corresponds to 30-100 ml of water, more preferably 40-50 ml.

6. The preparation method according to claim 2, characterized in that: The reaction temperature in step (2) is 80 to 180° C., preferably 90 to 120° C., and more preferably 100° C.; the reaction time is 12 to 72 hours, and preferably 24 hours.

7. The preparation method according to claim 2, characterized in that: The ruthenium precursor in step (3) is at least one of ruthenium chloride and ruthenium acetate.

8. The method according to claim 2, characterized in that: In step (3), the molar ratio of the rod-shaped rare earth metal oxide carrier to the ruthenium element in the ruthenium precursor is 50 to 60:

1.

9. Use of the rod-shaped rare earth metal oxide supported ruthenium catalyst as claimed in claim 1 or the rod-shaped rare earth metal oxide supported ruthenium prepared by the method as claimed in any one of claims 2 to 8 in the production of hydrogen by decomposing ammonia.

10. According to the use of claim 9, the ammonia decomposition hydrogen production reaction is at 300-450°C.

Citation Information

Patent Citations

  • Ru / Y2O3-MgO composite catalyst as well as preparation method and application thereof

    CN118513026A

  • Rare earth metal oxide supported ruthenium catalyst for ammonia decomposition to produce hydrogen and preparation and application

    CN109954493A

  • Ce-doped copper oxide loaded Ru ammonia decomposition hydrogen production catalyst and preparation method thereof

    CN118454690A

  • Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst

    CN119186590A

Cited By

  • Ruthenium atom cluster composite catalyst for hydrogen production through ammonia decomposition and preparation method of ruthenium atom cluster composite catalyst

    CN120394060A